FAKTOR-FAKTOR RISIKO KEJADIAN GAGAL GINJAL KRONIK (GGK) DI RUANG HEMODIALISA (HD) RSUP H. ADAM MALIK MEDAN - Solihuddin Harahap (Jurnal Online Keperawatan Indonesia, 2018)
Patients with chronic kidney disease are increasing and becoming the world’s problem. In 2015, at least 249 patients are being treated in hemodialysis room in RSUP H. Adam Malik Medan.Therefore, a research needs to be conducted to know what the risk factors that can cause of chronic kidney disease in hemodialysis room at RSUP H.Adam Malik Medan in 2016.The objective of this research is to identify the risk factors that triggered chronic kidney disease towards the patients in 2016 at RSUP H. Adam Malik Medan. Type of draft research are descriptives with cross sectional, 37samples were taken by purposive- sampling method.Mostly, chronic kidney diseaseoccurs at age of 46-55 years old (27%), do not have smoking habit (64,9%),not obese (62,2%), hypertension (81,1%), and do not have Diabetes Mellitus (81,1%).It is recommended for community to control their blood pressure and to modify the changeable risk factor, next researcher can do research with different variabels, and medical center can control the risk factor of chronic kidney disease.